From Aceh for Nusantara: The Contribution of Ulama Acehâs Work in Integration-Interconnection of Science - mubarak, husni (Center for Research and Development of Religious Literature and Heritage, 2017)
This paper elaborates more about the worldview which fulfill Ulama and Muslim scholarsâ mind in the archipelago at the past time, especially in Aceh by reviewing books and classics legacy. There are at least two books that became stressing of the study, i.e. Taj al-Mulk a-Murashsha bi Anwai al-Durar wa al-Manzhumat authored by Abbas Al-Asyi and Jamu Jawami al-Mushannafat (Eight Books), edited by Ismail Al-Asyi. By using the historical-philological approach, this paper tries to find and identify the Aceh classic manuscripts written around the XVIII and XIX century AD associated with traditions and Ulamaâs worldview two centuries ago which related to the science and knowledge. Even though Muslim scholars and Ulama in Aceh at the past time, mostly gave greater focus and attention on religious science such as fiqh (Islamic law) and tasawuf (Sufism) as both well known and shown in the work of Ar-Raniry and Fansuri, but basically they had an integrated worldview of Islamic science without fragmented. Although modernism and secularism which constructed in the West and then developed and introduced to the East, have been sorting and dichotomizing of science, but through the past work of Ulama Aceh which have huge contribution to the development of science paradigm in the archipelago, showed that there is very good and harmonious relationship between the various knowledge, religion and science.